The effect of superplasticizers on rheology and early hydration kinetics of rice husk ash-blended cementitious systems. (30th September 2017) - Msinjili, Nsesheye Susan; Schmidt, Wolfram; Mota, Berta; Leinitz, Sarah; Kühne, Hans-Carsten; Rogge, Andreas
Highlights: RHA in a blended system is experimented with three types of superplasticizers. The effect of PCE to RHA blended systems significantly lowers the yield stress. The workability of RHA in a blended system performs better with lignosulphonates especially over time. More precipitation of ettringite in RHA blended systems is observed with PCE. Further C-S-H growth in RHA blended systems is observed with lignosulphonate. Abstract: Superplasticizers (SPs) have been employed in concrete technology for decades to improve the workability of concrete in its fresh state. The addition of SPs in cement-based systems affects the early properties. Although the interaction of the cement particles with various SPs has been extensively researched, there still exists limited research on the interaction of SPs with supplementary cementitious materials such as rice husk ash (RHA). This paper investigates the rheological properties and early hydration kinetics of RHA-blended systems with three types of SPs, a polycarboxylate ether (PCE) and two lignosulphonates (LS-acc and LS-ret). In rheological properties, the addition of SP causes an initial improvement of workability as the yield stress is significantly reduced. The pastes with PCE and LS-acc show a slight increase of yield stress over time whereas pastes with LS-ret tend to lower the yield stress slightly over time, further improving the workability. Without SP, pastes with RHA show a lower yield stress but an increase in plastic viscosity as cement is further replaced with RHA. The addition of the LS SPs is observed to lower the plastic viscosity but remains constant with further replacement of cement with RHA. This indicates that LS SPs further adsorbs on RHA particles and hydration products produced causing dispersion of the particles within the system. In early hydration kinetics, pastes with PCE retard hydration and the degree of retardation is further increased with LS SPs. In the presence of RHA, the retardation of LS SP systems is significantly reduced. The pastes with PCE show more ettringite in the SEM micrographs, but is observed to be shorter needles. This indicates an initial good workability for PCE. However, C-S-H and CH were observed to be low in quantity, whereby the pastes with LS show more nucleation sites for C-S-H and CH. The ettringite needles in the LS systems were similar in quantity and more elongated in some cases but not abundant as in the PCE systems.